2003
DOI: 10.1029/2002jd002604
|View full text |Cite
|
Sign up to set email alerts
|

An estimate of the impact of stratosphere‐to‐troposphere transport (STT) on the lower free tropospheric ozone over the Alps using 10Be and 7Be measurements

Abstract: [1] In the framework of the European project STACCATO, combined measurements of 10 Be and 7 Be were carried out regularly during a full year at the high-altitude stations, Jungfraujoch (JUN), Switzerland and Zugspitze (ZUG), Germany. Inspection of the variability of the ratio 10 Be/ 7 Be in relation to 10 Be, 7 Be, and relative humidity (RH) reveals that the ratio is independent from processes that have a clear effect on both radionuclides, such as wet scavenging. High ratio values are generally met under c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 24 publications
4
83
0
Order By: Relevance
“…The model calculation (see SI Text) shows that nearly 40% of stratospheric air mass must mix into the free troposphere to increase the 35 SO 4 2− activity to 1;500 atoms m −3 as observed on March 28. This is highly unlikely because most of the stratospheric air mass (90%) returns back to the stratosphere within 6 h of crosstropopausal exchange (12), and only a small fraction (1-10%) is entrained into the free troposphere (10,12,13). In addition, relative humidity and surface ozone concentrations do not exhibit any noticeable change at SIO during the sampling time period typically associated with stratospheric incursions.…”
Section: Resultsmentioning
confidence: 99%
“…The model calculation (see SI Text) shows that nearly 40% of stratospheric air mass must mix into the free troposphere to increase the 35 SO 4 2− activity to 1;500 atoms m −3 as observed on March 28. This is highly unlikely because most of the stratospheric air mass (90%) returns back to the stratosphere within 6 h of crosstropopausal exchange (12), and only a small fraction (1-10%) is entrained into the free troposphere (10,12,13). In addition, relative humidity and surface ozone concentrations do not exhibit any noticeable change at SIO during the sampling time period typically associated with stratospheric incursions.…”
Section: Resultsmentioning
confidence: 99%
“…This feature was observed on all three flights during spring and thus seems not to be an individual outlier. Furthermore, in the time from April to July stratospheric mass transport into the upper and mid-troposphere is known to occur regularly (Appenzeller and Holten, 1996;Allen et al, 2003;Zanis et al, 2003;Olsen et al, 2004;Schoeberl, 2004). Moreover, Sprenger et al (2003) and Sprenger and Wernli (2003) demonstrated that cross-tropopause mass flux is highest in the midlatitudes where these mercury profiles were measured.…”
Section: North Americamentioning
confidence: 94%
“…The ratio 10 Be/ 7 Be shows a seasonal cycle with a clear maximum in May and June at Jungfraujoch, which is less pronounced at Zugspitze. Normally this ratio increases during stratospheric intrusion episodes, but an error propagation analysis [Zanis et al, 2003a] shows that, using the Dibb et al [1994] method, the stratospheric contribution to the surface O 3 can be estimated from these data with large uncertainties only.…”
Section: Climatologies Of Stementioning
confidence: 99%